European Fire Ant, Red Ant (suggested common names), Myrmica rubra Linnaeus (Insecta: Hymenoptera: Formicidae: Myrmicinae) - H. Alejandro Arevalo; Eleanor Groden (EDIS, 2007)
EENY-410, a 5-page illustrated fact sheet by H. Alejandro Arevalo and Eleanor Groden, is part of the Featured Creatures collection. It describes this adventive stinging ant found mainly in the northeastern U.S. Includes sections on synonymy, distribution, description, life cycle, economic importance, and management. Includes selected references. Published by the UF Department of Entomology and Nematology, August 2007.